2022
DOI: 10.3390/land11020205
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Recreational and Cultural Ecosystem Services Value of Islands

Abstract: With the gradual expansion of benefits provided by islands to human wellbeing, it has become increasingly important to quantify the cultural ecosystem service functions of islands. In this study, the zone travel cost method (ZTCM) and individual travel cost method (ITCM) are used to assess the recreational and cultural ecosystem services value of the island region of Changhai County, China, and the recreational value of Xiaochangshan, Dachangshan, and Guanglu Islands based on questionnaire survey data. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Though the majority of the land in the study area is primarily used for the cultivation of food crops, livestock rearing and plantations, it also provides services including biofuel, fiber, opportunities to store carbon, biodiversity, and recreational and aesthetic values [ 53 , 54 ]. Nevertheless, monoculture plantations of Eucalyptus can result in disturbance of the natural ecosystem and loss of ecosystem services [ 55 ]. This infers that the conservation of biodiversity and ecosystems is quite important for ensuring the improved livelihood and social welfare of the population [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though the majority of the land in the study area is primarily used for the cultivation of food crops, livestock rearing and plantations, it also provides services including biofuel, fiber, opportunities to store carbon, biodiversity, and recreational and aesthetic values [ 53 , 54 ]. Nevertheless, monoculture plantations of Eucalyptus can result in disturbance of the natural ecosystem and loss of ecosystem services [ 55 ]. This infers that the conservation of biodiversity and ecosystems is quite important for ensuring the improved livelihood and social welfare of the population [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li and Lau [27] explored how the perceived sociocultural benefits of festivals articulate island tourism's production of a sense of place and its respective locality. Zhao et al [28] found that there are recreational and cultural ecosystem service values for island tourism. Eugenio and Rotarou [29] found that the key issues of island tourism are the governance and management of natural resources and tourism activities, the impacts of climate change, the diversification of economies, and the promotion of innovative and personalized tourist experiences.…”
Section: The Initial List Of Sustainable Island Tourism Evaluation Cr...mentioning
confidence: 99%
“…Qualitative description methods are more detailed and incorporate the actual needs of different populations, but the credibility of the results may be questionable. Secondly, the monetised value of the CES is assessed by evaluating the economic value [19][20][21]. Monetary value data is widely available and easily quantifiable, but the method makes it difficult to capture the value of CES in terms of social relations, sense of place, access to inspiration, etc., through economic or monetary values [22,23].…”
Section: Introductionmentioning
confidence: 99%